2017
DOI: 10.1186/s12862-016-0859-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the angiopoietin-like gene family in teleosts and their role in skin regeneration

Abstract: BackgroundThe skin in vertebrates is a protective barrier and damage is rapidly repaired to re-establish barrier function and maintain internal homeostasis. The angiopoietin-like (ANGPTL) proteins are a family of eight secreted glycoproteins with an important role in skin repair and angiogenesis in humans. In other vertebrates their existence and role in skin remains largely unstudied. The present study characterizes for the first time the homologues of human ANGPTLs in fish and identifies the candidates that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 87 publications
(105 reference statements)
2
17
1
Order By: Relevance
“…Cutaneous repair following scale removal involved morphological modifications similar to what was reported in gilthead sea bream (Costa et al, 2017;Vieira et al, 2011), sea bass (Guerreiro et al, 2013) and other teleosts (Ogawa et al, 2010;Ohira et al, 2007;Quilhac & Sire, 1999). No major histological and histomorphometric modifications were seen between control and chronically stressed fish in both regenerated and undamaged skin.…”
Section: Cutaneous Barrier Is Reestablished In Chronically Stressed Fsupporting
confidence: 70%
“…Cutaneous repair following scale removal involved morphological modifications similar to what was reported in gilthead sea bream (Costa et al, 2017;Vieira et al, 2011), sea bass (Guerreiro et al, 2013) and other teleosts (Ogawa et al, 2010;Ohira et al, 2007;Quilhac & Sire, 1999). No major histological and histomorphometric modifications were seen between control and chronically stressed fish in both regenerated and undamaged skin.…”
Section: Cutaneous Barrier Is Reestablished In Chronically Stressed Fsupporting
confidence: 70%
“…ANGPTL5 is structurally similar to other members of ANGPTL protein family, owning a cleavable signal peptide in N-terminal, a coiled-coil domain, and a fibrinogen-like domain. Like ANGPTL3 and 4 plays a role in lipid and triglyceride metabolism and vertebrate development [ 38 ]. The ANGPTL5 receptor is not yet known.…”
Section: Angptl Protein Family and Angiogenesismentioning
confidence: 99%
“…The ANGPTL5 receptor is not yet known. ANGPTL5 is mainly expressed in adipose tissue and adult human hearth [ 38 , 39 ]. Up to date, no data are published about its role in angiogenesis.…”
Section: Angptl Protein Family and Angiogenesismentioning
confidence: 99%
“…While Rh- and Amt-type transporters often co-occur in eukaryotic genomes, such co-occurrence has been rarely identified in bacterial genomes. Among the few exceptions are anaerobic ammonia oxidizers (anammox), which possess both types of transporters (Matassi 2017 ). Crystal structure analyses revealed that Amt- as well as Rh-type transporters form homotrimers with a central, hydrophobic pore (Khademi et al 2004 ; Lupo et al 2007 ; Zheng et al 2004 ).…”
Section: Differences In Nitrogen Acquisition and Assimilation In mentioning
confidence: 99%